Switching a pH indicator by a reversible photoacid: A quantitative analysis of a new two-component photochromic system. (February 2016) - Vallet, J.; Micheau, J.-C.; Coudret, C.
Abstract: A UV/visible and pH-metric quantitative analysis of the spiropyran reversible photoacid1 -MEH allowed us to determine the pKa 's of the open and closed forms, the rate constants of relaxation, the quantum yield of decolouration and the UV/visible spectra of the protonated and deprotonated open and closed isomers. The coupling between1 -MEH and a selected pH-indicator acidochromic dye via proton exchange has also been analysed. The initial pH, stoichiometric ratio between the photoacid and the pH-indicator, light intensity and pKa range of the pH-indicator have been established to maximize the proton transfer from the photoacid donor to the pH-indicator acidochromic dye acceptor. When the pKa 's are matched, the two-component system behaves like a single photochromic dye. The proposed model explains why1 -MEH photo-switches BromoCresol Green but not Methyl-Orange. Graphical abstract: The coupling between a simple water soluble spiropyran reversible photoacid and a pH indicator has been quantitatively analysed. The initial pH, stoichiometric ratio, light intensity and pKa range have been determined to maximize the proton transfer from the photochromic donor to the pH-indicator acceptor. Highlights: A water soluble reversible photochromic spiropyran photoacid was parametrized. Numerical fit was used to propose a plausible chemical network. In silico optimization was used to optimize the photoacid to a pH sensitive dye. Experimental verification was then achieved with standard pH indicators.